Soil stabilization using Silicon Carbide (SiC) nanoparticles: confirmation using XRD, SEM, and FTIR - Alsabhan, Abdullah H.; Qadri, Jibran; Sadique, Md Rehan; Alam, Shamshad; Perveen, Kahkashan; Binyahya, Abobaker Salem (Journal of Civil Engineering and Management, 2023)
The current research focuses on nanoparticles’ ground-improvement potential using clayey soil mixed with varying amounts of the nanoparticles “Silicon Carbide”. With an increase in the amount of nanomaterial, a tendency of improvement has been recorded in liquid and plastic limits, as well as the plasticity index. The maximum reduction in liquid limit (15.8%), plastic limit (13.6%), and plastic index (18.7%) was recorded at 0.25 gm of Silicon Carbide as compared to control (0 gm of SiC). There was a 26.7% and 33.3% increase in the cohesion of soil at 0.25 gm and 0.3 gm of Silicon Carbide, respectively. Furthermore, when the Silicon Carbide content increased from 0.25 gm, the rate of increment of friction angle also increased. It was 87.5% and 137.5% at 0.25 gm and 0.3 gm of Silicon Carbide, respectively. Furthermore, 0.3 gm of Silicon Carbide, is found to be optimal within the scope of the experiment as at this amount of Silicon Carbide both cohesion and angle of friction attained maximum. XRD, SEM, and FTIR were used to confirm the findings. It concludes that by using even a small amount of nanomaterial, an appreciable change in the properties of clayey soil can be obtained in the field. First published online 16 December 2022